Reciprocating grate energy plant revisited - Cheong, M. B. T., Duraserf (M) Sdn Bhd., 57-A, USJ 21/11, UEP Subang Jaya, 47620 Selangor (Malaysia) (Forest Research Institute Malaysia (FRIM), 2014)
The soaring cost of crude oil and climate change have made it attractive to replace fossil fuel with a renewable source of energy such as wood. Trees need carbon dioxide to form wood. Burning wood instead of fossil fuel has the effect of stabilizing the greenhouse gases in the atmosphere. Use of reciprocating grate energy plant is an efficient way to replace fossil fuel with renewable fuel. Why that is so is given by way of explaining the basic features of a modern energy plant, saving of production cost, safety features and environmental protection. The design criteria for a modern energy plant are discussed. As a result of the adoption of the Kyoto Protocol in 2005, there are new opportunities for industries that invest in energy plants to derive additional benefits by selling carbon credits.